'Make the terror behind greater than the terror in front'? Internal discipline, forced participation, and the I.R.A., 1919–21. Issue 161 (12th June 2018) - Hughes, Brian
Abstract: This article will explore two relatively neglected features of the Irish Republican Army's (I.R.A.) guerrilla war between 1919 and 1921: internal discipline and forced participation. The gravest disciplinary measure was the death penalty and I.R.A. orders directed that it should apply to members guilty of certain offences against the army. While British army and police officials often insisted that the I.R.A. executed its own without scruple, the death penalty was rarely carried out in practice. General Headquarters (G.H.Q.) was largely unsuccessful in applying a standard disciplinary code and there was also a general inconsistency and lack of rigour in applying other punitive measures for less serious offences. On a related theme, it was not uncommon for soldiers to be 'conscripted' or forced to take part in operations under duress during irregular warfare. In the Irish case, this idea has rarely been discussed. It will be argued here that, along with the death penalty and strict punitive measures, forced participation was an uncomfortable idea and often counter-productive in practice. The nature and extent of discipline and coercion was also firmly dictated by local conditions and personalities.